1991
DOI: 10.1111/j.1471-4159.1991.tb02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Myelin Proteolipid Protein Gene Alter Oligodendrocyte Gene Expression in Jimpy and Jimpymsd Mice

Abstract: The mouse myelin proteolipid protein (PLP) gene has been studied in normal and jimpymsd mice. Potential upstream regulatory regions of the normal gene have been cloned and mapped, but when these regions were studied in jimpymsd mice by Southern blots, no alterations were observed, relative to the normal gene. To assess whether the low ratio of PLP to DM20 proteins in this mutant reflected an altered PLP/DM20 ratio mRNAs, S1 nuclease analyses were undertaken, which demonstrated that at all ages studied in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 52 publications
4
41
0
Order By: Relevance
“…3). Previous studies [5] have shown that Plp gene transcription, in brain, is reduced in affected mice, with Plp jp mice at P25 having similar levels of Plp transcription as wild-type mice at P7. Other studies [38] have shown that the pattern of myelin gene expression in Plp jp oligodendrocytes is consistent with that found in immature wild-type cells.…”
Section: Downregulation Of the Plp Gene And The Plp(+)z Transgene In mentioning
confidence: 84%
See 4 more Smart Citations
“…3). Previous studies [5] have shown that Plp gene transcription, in brain, is reduced in affected mice, with Plp jp mice at P25 having similar levels of Plp transcription as wild-type mice at P7. Other studies [38] have shown that the pattern of myelin gene expression in Plp jp oligodendrocytes is consistent with that found in immature wild-type cells.…”
Section: Downregulation Of the Plp Gene And The Plp(+)z Transgene In mentioning
confidence: 84%
“…Campagnoni's group showed two decades ago that PLP protein and mRNA are dramatically downregulated in Plp jp mice [33][34][35]. Additionally, it has been known for some time that both Plp and Mbp transcriptional activity is decreased in the brains of affected males [5,36]. While the obvious assumption has been that the mutant PLP protein is responsible for this change, it is possible that the point mutation itself could have had a cis effect on Plp gene activity.…”
Section: Downregulation Of the Plp Gene And The Plp(+)z Transgene In mentioning
confidence: 99%
See 3 more Smart Citations